(untitled) (Indonesian Tourism Justice Review, 2024)
Tourism has long been seen as an economic driver, but its potential as a tool for social justice and community empowerment remains underexplored. This paper investigates how tourism in Indonesia can be harnessed to promote social justice by empowering marginalized communities. Focusing on community-based tourism initiatives in rural areas such as Flores, Sumba, and Aceh, the study examines how tourism can provide opportunities for local communities to gain economic independence, preserve cultural heritage, and improve their quality of life. The research explores the mechanisms through which community-run tourism enterprises can foster social cohesion, protect indigenous knowledge, and provide an alternative to exploitative tourism models. Drawing on case studies and interviews with local entrepreneurs, the paper evaluates the successes and challenges of these initiatives in promoting social justice. The study concludes by offering recommendations for policy changes that encourage the growth of community-based tourism models, ensuring that tourism serves as a tool for both economic and social empowerment.